2003
DOI: 10.1074/jbc.m309655200
|View full text |Cite
|
Sign up to set email alerts
|

A Product of the Human Gene Adjacent to parkin Is a Component of Lewy Bodies and Suppresses Pael Receptor-induced Cell Death

Abstract: Parkinson's disease (PD)1 is a movement disorder characterized pathologically as a progressive loss of dopaminergic neurons in the substantia nigra pars compacta. Most cases of PD are sporadic, and the etiology of common PD remains unknown. However, recent identification of gene mutations in familial cases of PD has advanced our understanding of the molecular mechanisms behind the neurodegeneration associated with this disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(52 citation statements)
references
References 31 publications
5
47
0
Order By: Relevance
“…Pacrg is also expressed in several mouse tissues other than testes, although at much lower levels (data not shown). Confirming previous reports (25,26), our Northern blot analysis detected human PACRG mRNA in several tissues, including the brain. However, our study shows that the PACRG transcript is most abundant in testes, indicating that this gene may play a role in human spermiogenesis as well.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…Pacrg is also expressed in several mouse tissues other than testes, although at much lower levels (data not shown). Confirming previous reports (25,26), our Northern blot analysis detected human PACRG mRNA in several tissues, including the brain. However, our study shows that the PACRG transcript is most abundant in testes, indicating that this gene may play a role in human spermiogenesis as well.…”
Section: Discussionsupporting
confidence: 75%
“…6). In agreement with both of these observations, Pacrg appears to localize to axonal processes and cytoplasmic vesicles in neuronal cells (26). It is possible that in the testis Pacrg may be necessary for the proper association between the membrane structures (i.e., plasma membrane and nuclear envelope) and the microtubular elements of the spermatid (i.e., manchette and nuclear ring), which are thought to be involved in head shaping during spermiogenesis.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…In support of this idea, previous studies have provided indirect evidence for PACRG-tubulin interaction. For example, Imai et al [3] detected a-and b-tubulin as PACRG-associated proteins by immunoprecipitation from the lysates of human embryonic kidney cells that over-express PACRG. In addition, Taylor et al [4] showed that the localization of PACRG in neurons of the locus coeruleus in the progressive supranuclear neuron palsy brain is displaced by hyperphosphorylated tau, a microtubule-associated protein [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…PACRG has been suggested to interact with Parkin/Park2 and form a large chaperonin complex with chaperones [3]. Taylor et al [4] showed that PACRG is regulated by a ubiquitin-proteasomal system that involves Parkin/Park2.…”
Section: Introductionmentioning
confidence: 99%